How should donors manage adaptively? Market Systems Development as a case study. - Itad (Itad, 2018)
Itad has recently completed a strategic evaluation for Sida to help them work through how they can best manage programmes that are adaptive and apply systems approaches - the conclusions from the evaluation about what funders need to do to manage adaptively are of broader relevance.

Debiasing: a systematic discipline and delight for development professionals - Chambers, Robert (Institute of Development Studies, 2018)
Do we really need debiasing, yet another word?  Yes, unless anyone can improve on it, because we need a word to describe a rigorous discipline we development professionals need for grounded realism. This has been coming on me slowly. But now explorations and ‘aha!’ moments in India have accumulated and combined into an epiphany.  For […]

Transformative Networks Are Multiscalar - Holley, June (NetworkWeaver, 2018)
This is an excerpt from the Network Weaver Handbook. I’ll be writing an update with my latest research and thinking on the topic in the coming weeks so stay tuned!     June Holley How does tr…

Doing Development Differently in the Global South - Workshop Report - CARE (CARE and British Council, 2018)

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume II: Case studies - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Volume 3: Participatory Monitoring, Evaluation, and Learning in Complex Adaptive Environments - SACE (SACE Program, 2018)
This volume is the last in a series of papers about systems approaches in complex environments, which includes the use of the collective impact model to address large-scale social problems, and the application of participant-driven MEL techniques across 17 networks of civil society organizations. It is based on the experiences of Root Change and Chemonics, two development partners working on a USAID civic engagement project in Nigeria (2013-2018), as well as hundreds of civil society organization partners. This is the final paper in the series and aims to highlight how the adaptation of participatory monitoring, evaluation, and learning techniques (e.g., most significant change, outcome mapping, and outcome harvesting) evolved and ultimately empowered cluster members. The first paper in the series presented a brief introduction to systems approaches in advocacy settings, the SACE theory of change, and the scope of Root Change’s work as technical lead on capacity building and measurement. The second volume aims to address the innovative use of the advocacy strategy matrix, adapted from work by the Center for Evaluation Innovation, for collective impact and the Collective Impact Model, an approach that engages multiple players in working together to solve complex social problems.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Old Wine in New Bottles? 6 ways to tell if a programme is really ‘doing development differently’ - Green, Duncan (From Poverty to Power, 2018)
Some top adaptive management exponents give their top tips on how to distinguish spin from reality, when looking at an avowedly AM programme

Thinking and working with political settlements. The case of Tanzania - Kelsall, Tim (Working Paper, 2018)
The institutions and power relations that underpin political stability are crucial shapers of development outcomes, to which aid policy ought to adapt. • This paper trials a new political settlements concept, based on the idea that settlements can be distinguished according to the breadth and depth of their social foundation, and the degree to which they concentrate power. • Since independence, Tanzania has oscillated between broad-dispersed and narrow-concentrated political settlements and is currently moving in the direction of a more narrow and concentrated settlement than ever before. • The opportunities for international donors to change this direction of travel appear limited. Adapting to it implies providing financial and technical support to central government, while trying to strengthen the policy role of non-state actors in non-confrontational ways. • In recent years, Political Settlements Analysis (PSA) has become increasingly influential in academic and policy circles • Despite its intuitive appeal, it seems difficult to use in practice • PSA has a natural affinity with Adaptive Development, Thinking and Working Politically, and Doing Development Differently approaches • By answering the simple diagnostic questions supplied here, development partners can identify the types of political settlements in which they work, and draw some broad operational implications

Sample criteria to select case studies for evaluation - Methods Lab (2018)
Time and budget constraints often mean that organisations are unable to evaluate all of their programmes, and large programmes, operating in multiple locations, are unable to evaluate all project sites. This tool introduces two sets of criteria to support evaluators and programme managers to select case studies or programmes for evaluation: i) information about how relevant or feasible evaluation is for individual programmes, and ii) across the overall portfolio, strategic thinking around what types of cases are most important to understand. This tool was developed by Anne Buffardi, Irene Guijt, Simon Hearn and Tiina Pasanen for use in The Methods Lab projects.

Outcome Mapping FAQs - Outcome Mapping Learning Community (Outcome Mapping, 2018)
FAQ resource produced by IDRC's Evaluation Unit, with contributions from Kaia Ambrose, Sarah, Earl, Jan Van Ongevalle and Julius Nyangaga. We've added it here to answer some of your OM related questions.

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Representing theories of change: technical challenges with evaluation consequences - Davies, Rick (Journal of Development Effectiveness, 2018)
This paper looks at the technical issues associated with the representation of Theories of Change and the implications of design choices for the evaluability of those theories. The focus is on the description of connections between events rather than the events themselves, because this is seen as a widespread design weakness. Using examples and evidence from Internet sources six structural problems are described along with their consequences for evaluation. The paper then outlines a range of different ways of addressing these problems that could be used by programme designers, implementers and evaluators. The paper concludes with some caution speculating on why the design problems are so endemic but also pointing a way forward. Four strands of work are identified that CEDIL and DFID could invest in to develop solutions identified in the paper.
Keywords: Evaluation; evaluability; representation; theory of change

Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation

Iterative Design and Monitoring for Adaptive Management: How Causal Link Monitoring can help - Britt, Heather; Hummelbrunner, Richard; Green, Jackie (Better Evaluation, 2018)
Development actors are embracing the concept and practice of adaptive management, using evidence to inform ongoing revisions throughout implementation. In this guest blog, Heather Britt, Richard Hummelbrunner and Jackie Greene discuss a practical approach that donors and partners can use to agree on what’s most important to monitor as a project continues to evolve.

Sounding clever or being smart? – How to do more with less in evaluating governance programmes - Aston, Tom (Care Insights, 2018)
About a decade ago, the development sector fell into the same trap the financial services industry did in the mid-1990s. We were all seduced by clever...

The role of research and learning in adaptive programming - Babon, Andrea; Denney, Lisa (Devpolicy Blog from the Development Policy Centre, 2018)
Andrea Babon and Lisa Denney explore how learning partners - a common feature of aid programs - can operate and feed into programs.

Monitoring and evaluation for adaptive programming - Roche, Chris; Kelly, Linda (Devpolicy Blog from the Development Policy Centre, 2018)
Chris Roche and Linda Kelly with six take-aways on what is being tried and learnt in setting up monitoring and evaluation frameworks for adaptive programs.

Walking the adaptive talk - Denney, Lisa (Devpolicy Blog from the Development Policy Centre, 2018)
The first in a three-part series on adaptive aid.Lisa Denney clarifies the confusion.

Learning to make a difference: Christian Aid Ireland’s adaptive programme management in governance, gender, peace building and human rights - Booth, David; Balfe, Karol; Gallagher, Róisín; Kilcullen, Gráinne; O'Boyle, Sarah; Tiernan, Alix (ODI, 2018)
This paper assesses the relevance of adaptive or trial-and-error approaches to the field of governance, peace building and human rights. Tackling the problems of poverty, vulnerability and exclusion that persist in parts of the world that continue to be affected by violence or political insecurity is difficult for several reasons. For one, because of the complexity of the prevailing social, economic and political systems, solutions to chronic problems are far from obvious. One response to this aspect of the challenge is adaptive programme design and management. This paper is the product of a multi-year collaboration between ODI and the core team of Christian Aid Ireland to assess the relevance of adaptive or trial-and-error approaches to the field of governance, peace building and human rights. It explains the basis on which Christian Aid Ireland’s current five-year programme has become committed to an adaptive approach. It then describes and seeks to draw lessons from the programme’s first year of experience, considering the possible implications for implementation over the coming years. The authors find that to get full benefits from the move to adaptive management, the new ways of working and their underlying principles will need to become more embedded in organisational practices and cultures.

Building a global learning alliance on adaptive management - Wild, Leni; Ramalingam, Ben (ODI, 2018)

Q&A: Complexity-Aware Planning for Stabilization Programming - Martins, Christy (DAI - Checkpoint, 2018)

Opportunities for Using Complexity-Aware Approaches to Theory of Change - Goodier, Sarah; Apgar, Marina (SDC-IDS Briefing Note 8, 2018)
The purpose of this briefing note is to review opportunities for using complexity aware approaches to Theory of Change (ToC) to inform the SDC approach. It provides an overview of complexity-aware approaches and then focuses on demonstrating how complexity thinking can support programming by building on the frameworks currently being used in the project/programme cycle management (PCM) processes. It is aimed at SDC staff, in particular Programme Officers and staff of partner organisations involved in the management of SDC interventions.

State of the Art on Use of Theory of Change in the Development Sector - Goodier, Sarah; Apgar, Marina; Clark, Louise (SDC-IDS Briefing Note 7, 2018)
The purpose of this briefing note is to add to SDC’s understanding of Theory of Change (ToC), drawing on the literature and practice to sketch out the current state of the art approach. This involves expanding on ToC beyond SDC’s current practice of using Impact Hypotheses (IH) to bridge it to operational practice and use ToC more explicitly in the project/programme cycle management (PCM) processes. Sharing the state of the art on use of ToC in the development sector, this briefing note outlines what a ToC is, what it is used for and why it is needed in the development sector. It discusses ToC as both a process and a product, providing step by step guidance on how to facilitate a ToC process. The differences between a ToC and a logframe are highlighted. Some key criteria for recognising when you have a ‘good’ ToC are also included. This brief is aimed at SDC staff, in particular Programme Officers, and staff of partner organisations involved in the management of SDC interventions.

Using adaptive monitoring, evaluation and learning in programme design - Nzegwu, Femi (INASP, 2018)

Making humanitarian response more flexible: Challenges and questions - Obrecht, Alice; Bourne, S. (ALNAP/ODI, 2018)

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Simplicity, Accountability and Relationships: Three ways to ensure MEL supports Adaptive Management - Roche, Chris (From Poverty to Power, 2018)
Based on a recent discussion in Manila, Chris Roche reflects on how Monitoring, Evaluation and Learning can better support 'adaptive programming'.

MLE or MEL in adaptive programming? - Pellini, Arnaldo (Knowledge counts, 2018)

Twinning “Practices of Change” With “Theory of Change”: Room for Emergence in Advocacy Evaluation - Arensman, Bodille; van Waegeningh, Cornelie; van Wessel, Margit (American Journal of Evaluation, 2018)
Theory of change (ToC) is currently the approach for the evaluation and planning of international development programs. This approach is considered especially suitable for complex interventions. We question this assumption and argue that ToC’s focus on cause–effect logic and intended outcomes does not do justice to the recursive nature of complex interventions such as advocacy. Supported by our work as evaluators, and specifically our case study of an advocacy program on child rights, we illustrate how advocacy evolves through recursive interactions, with outcomes that are emergent rather than predictable. We propose putting “practices of change” at the center by emphasizing human interactions, using the analytical lenses of strategies as practice and recursiveness. This provides room for emergent outcomes and implies a different use of ToC. In this article, we make a clear distinction between theoretical reality models and the real world of practices.

In pursuit of the deep and sustained shifts necessary for adaptive management - Simister, Nigel (INTRAC, 2018)
The final blog in Nigel Simister's series on adaptive management and the M&E of complex projects and programmes.

How Decent is Decent Work? Using SenseMaker to understand workers’ experiences - Mager, Franziska; Smith, Becca; Gujit, Irene (Oxfam, 2018)

How Adaptive Management is challenging the monitoring and evaluation of complex programmes - Simister, Nigel (INTRAC, 2018)
By Nigel Simister Adaptive management is a broad approach designed to support development or humanitarian programmes in complex or uncertain …

Approaches for addressing complexity in programme theory: Experiences in applying the Actor-based Change (ABC) Framework to a variety of international development programmes and evaluations - Koleros, Andrew; Oldenbeuving, Mark (UK Evaluation Society 2018 Annual Evaluation Conference, 2018)

How do we know what works? Interview with Prof. Michael Woolcock, Lead Social Scientist at the World Bank - Evans, Alice (2018)
Dr Alice Evans and leading experts discuss growth, governance, & gender inequalities. Alice is a Lecturer at King's College London, and Faculty Associate at the Harvard Kennedy School.

Thinking big: How to use theory of change for systems change - Abercrombie, Rob; Boswell, Katie; Thomasoo, Rosanna (NPC, 2018)
We think that, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of change, and walks through five rules of thumb that will help organisations to use the approach to tackle complex problems. We think that, applied well, theory of change can support charities and funders to take a systemic approach to their work. This report identifies five common pitfalls that organisations fall into when using theory of change, and walks through five rules of thumb that will help organisations to use the approach to tackle complex problems.

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

The Debate about RCTs in Development is over. We won. They lost. - Pritchett, Lant (DRi Seminar, 2018)
There has been a debate in development economics over the last 20 years as some claimed the use of RCTs as a tool for independent impact evaluation would significantly improve development practice and hence development. While right about the methodological claims about the superiority of randomization to produce cleaner estimates of the LATE (local average treatment effect) of projects and programs, this, in and of itself, does not change development practice. All of the five claims needed to sustain a positive model in which RCT/IIE has a major positive impact are demonstrably false. The proponents of RCTs have responded to losing the first round decisively by changing significantly both their claims and their practice.

Why We Lie About Aid: Development and the Messy Politics of Change - Yanguas, Pablo (Zed Books, 2018)
Foreign aid is about charity. International development is about technical fixes. At least that is what we, as donor publics, are constantly told. The result is a highly dysfunctional aid system which mistakes short-term results for long-term transformation and gets attacked across the political spectrum, with the right claiming we spend too much, and the left that we don't spend enough. The reality, as Yanguas argues in this highly provocative book, is that aid isn't – or at least shouldn't be – about levels of spending, nor interventions shackled to vague notions of ‘accountability’ and ‘ownership’. Instead, a different approach is possible, one that acknowledges aid as being about struggle, about taking sides, about politics. It is an approach that has been quietly applied by innovative development practitioners around the world, providing political coverage for local reformers to open up spaces for change. Drawing on a variety of convention-defying stories from a variety of countries – from Britain to the US, Sierra Leone to Honduras – Yanguas provides an eye-opening account of what we really mean when we talk about aid.

OPM’s approach to assessing Value for Money - King, Julian; OPM (Oxford Policy Management, 2018)
This document offers practical guidance for assessing value for money (VfM) in international development programmes. Since 2016, evaluation expert Julian King has been working with OPM to develop and deploy a robust approach to VfM assessment. The approach combines cutting-edge evaluation practice with concepts from economic evaluation to respond to donor requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management.

Case Study Research and Applications: Design and Methods - Yin, Dr Robert K. (SAGE Publications, Inc, 2018)
Winner of the 2019 McGuffey Longevity Award from the Textbook & Academic Authors Association (TAA) Recognized as one of the most cited methodology books in the social sciences, the Sixth Edition of Robert K. Yin′s bestselling text provides a complete portal to the world of case study research. With the integration of 11 applications in this edition, the book gives readers access to exemplary case studies drawn from a wide variety of academic and applied fields. Ultimately, Case Study Research and Applications will guide students in the successful use and application ofthe case study research method.

The Whistler principles to accelerate innovation for development impact - G7 (G7, 2018)
The Whistler principles to accelerate innovation for development impact : 2018 G7 Summit – Canada 2018 G7 Presidency – Charlevoix, Quebec

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

The rise of the randomistas: on the experimental turn in international aid - Donovan, Kevin P. (Economy and Society, 2018)
In recent years, the use of experimental methodologies has emerged as a central means of evaluating international aid interventions. Today, proponents of randomized control trials (so-called randomistas) are among the most influential of development experts. This paper examines the growth of this thought collective, analysing how uncertainty has become a central concern of development institutions. It demonstrates that transformations within the aid industry – including the influence of evidence-based policy, the economization of development and the retreat from macro-planning – created the conditions of possibility for experimentation. Within this field, the randomistas adeptly pursued a variety of rhetorical, affective, methodological and organizational strategies that emphasized the lack of credible knowledge within aid and the ability of experiments to rectify the situation. Importantly, they have insisted on the moral worth of experimentation; indeed, the experimental ethic has been proposed as the way to change the spirit of development. Through causal certitude, they propose to reduce human suffering. The rise of experimentation has not, however, eliminated accusations of uncertainty; rather, it has redistributed the means through which knowledge about development is considered credible.
Keywords: Development; Evidence; Experimentation; aid; uncertainty

Developmental evaluation: Bridging the gaps between proposal, program, and practice , Developmental evaluation: Bridging the gaps between proposal, program, and practice - Lawrence, Rachael B.; Rallis, Sharon F.; Davis, Laura C.; Harrington, Karen (Evaluation, 2018)
Developmental evaluation supports grant-funded initiatives seeking innovation and change. Programs born from aspirational grant language and plans often need guidance as they work toward creating workable models for social innovation. This article describes the challenge of designing and implementing complex programs and presents a case that illustrates how a program moves from proposal to practice. The Massachusetts Charter Public School Association Capacity Building Network is a complex intervention, funded by the US federal government, aimed at raising school capacity to serve students with disabilities and English language learners. Developmental evaluation served to bridge the gaps between an aspirational proposal, an ambitious and ambiguous program plan, and emerging practices to serve this population of students. Jointly reviewing our experience in this developmental evaluation, the evaluation team and a program director share important thematic lessons learned about the developmental evaluation approach., Developmental evaluation supports grant-funded initiatives seeking innovation and change. Programs born from aspirational grant language and plans often need guidance as they work toward creating workable models for social innovation. This article describes the challenge of designing and implementing complex programs and presents a case that illustrates how a program moves from proposal to practice. The Massachusetts Charter Public School Association Capacity Building Network is a complex intervention, funded by the US federal government, aimed at raising school capacity to serve students with disabilities and English language learners. Developmental evaluation served to bridge the gaps between an aspirational proposal, an ambitious and ambiguous program plan, and emerging practices to serve this population of students. Jointly reviewing our experience in this developmental evaluation, the evaluation team and a program director share important thematic lessons learned about the developmental evaluation approach.

Collaboration for Impact (2018)
The site seeks to accelerate the adoption of system collaboration and Collective Impact in Australia. It does so by creating knowledge, network and tools; shining a light on successful Collective Impact initiatives; and building an Australian community of practice.

MIRADI: Adaptive Management Software for Conservation Projects (2018)

NetworkWeaver (NetworkWeaver, 2018)
Weaving Smart Networks

Combining Big Data and Thick Data to Improve Services Delivery - Ang, Yuen Yuen (IBM Center for The Business of Government, 2018)

Evaluating interventions that prevent or counter violent extremism: A practical guide - Hofman, Joanna; Sutherland, Alex (RAND Corporation, 2018)

Evaluating Systems Change Results: an inquiry framework - Cabaj, Mark (Tamarack Institute, 2018)

GIZ’s evaluation system - GIZ Evaluation Unit (GIZ GmbH, 2018)
This provides a general description of GIZ’s new evaluation system, which is designed to implement our new policy and to achieve the objectives of evaluation reform. This general description is accompanied by two other documents that provide supplementary details of GIZ’s key evaluation instruments: project evaluations for BMZ business and corporate strategic evaluations. They are geared in particular to GIZ staff members who commission, implement or support evaluations and to evaluators who conduct evaluations on behalf of GIZ as well as repre-sentatives of commissioning parties, clients and cooperation partners. The current versions are very much a ‘work in progress’ in many regards. We are well aware that we will only be able to meet our own high expectations of our evaluations if we continue to develop their quality in dialogue with project staff, our commissioning parties, clients and partners and with evaluation practitioners and experts from the academic, scientific and research community. We look forward to taking on this task and to sharing our experience with all interested parties.

Tips for Finding Unusual Allies and Building Innovative Alliances - Jacobstein, David (USAID Learning Lab, 2018)
One of the truisms of thinking and working politically (TWP) is that it requires looking differently at how stakeholders relate to a given development challenge or process, and building coalitions of the “right actors at the right time” who can drive forward progress while working with the grain of the context. While it’s easy to call for coalitions for change and diverse stakeholder engagement, identifying allies beyond those already seized with an issue, and finding ways to collaborate with stakeholders who may have different reasons for joining a coalition, is a challenging task. These are some suggested tips to improve working in that fashion.

Regional Healthcare Ecosystem Analyst for Healthcare Associated Infections - Lee, Bruce Y. (Grantome, 2018)
Understanding and preventing the spread of both endemic and emerging healthcare-associated infectious diseases throughout hospitals and nursing homes is a national priority. Our work has shown that the many disparate inpatient healthcare facilities in a region can form a complex healthcare ecosystem connected by both direct and indirect patient sharing allowing pathogens in one health care facility to readily spread to other facilities. Our goal is to further develop RHEA (Regional Healthcare Ecosystem Analyst) into a user-friendly software tool that decision makers (e.g., policy makers, funders, product developers and manufacturers, healthcare administrators, infection prevention specialists, researchers, and educators) can readily use to help healthcare ecosystems prevent and control the spread of an endemic pathogen, methicillin- resistant Staphylococcus aureus (MRSA), and an emerging pathogen, carbapenem-resistant Enterobacteriaceae (CRE). This next generation of RHEA will bring multiple innovations by: 1) further elucidating the interconnectedness of the ecosystem and showcasing the value of cooperation among facilities versus the current individual facility approach to infectious disease control, 2) incorporating new healthcare ecosystem responses for endemic MRSA and emerging CRE, 3) continuing our work integrating economic and operational models into a framework of infectious disease epidemiological models, 4) imbuing virtual patients with characteristics linked to MRSA and CRE transmission and outcome risk, 5) building a comprehensive """"""""virtual laboratory"""""""" to help address many existing and future healthcare ecosystem infectious disease questions, and 6) building a user-friendly modeling tool that decision makers can use. The project will continue our team's longstanding modeling work and developing computational tools for decision makers via three specific aims. First, completing Specific Aim 1 will expand RHEA by adding the following capabilities: i) integrated clinical outcome and economic models, ii) more extensive and detailed patient characteristics linked to changes in infection risk and costs, iii) expanded HAI control measures, and iv) stochastic and adaptive disease parameters to represent emerging and evolving diseases. Next, Specific Aim 2 will use our newly expanded RHEA framework to model a sample endemic pathogen, MRSA, and a sample emerging pathogen, CRE to identify optimal control strategies even when pathogen characteristics are evolving. Finally, Specific Aim 3 will involve developing a user-friendly interface for RHEA and deploying it as a healthcare ecosystem computational modeling tool that various stakeholders (e.g., policy makers, healthcare administrators, infection control specialists, funders, and product manufacturers) can readily use to make decisions regarding the control of healthcare-associated infections. Public Health Relevance Understanding and preventing the spread of healthcare-associated infectious diseases throughout hospitals and nursing homes is a national priority. Simulation models can serve as virtual laboratories to help identify best practice solutions for containing common [such as methicillin-resistant Staphylococcus aureus (MRSA)] and emerging [e.g., carbapenem-resistant Enterobacteriaceae (CRE)] causes of healthcare associated infections (HAIs). Our goal is to develop our software RHEA (Regional Healthcare Ecosystem Analyst) into a computational modeling tool that can be used directly by decision makers to identify, develop, and evaluate strategies and interventions to reduce HAIs across a large geographic region.

Developing and Using Useful ToCs - Mayne, John (Evergreen Briefing Note, 2018)
Developing useful theories of change (ToCs) for anintervention, especially complex interventions, is not straightforward nor something done in a couple of hourswith limited effort. Agreement is needed on a number of basic concepts and terms, key challenges need to be addressed, and there are numerous issues that need to be considered.Butthe effort is worth the investment of resources and time.Theory-based evaluation approaches need good ToCs.Some of the ideas here are discussed in the context of agricultural research for nutrition and health interventions by Mayne and Johnson (2015) (10) Developing and Using Useful ToCs. Available from: https://www.researchgate.net/publication/323868372_Developing_and_Using_Useful_ToCs [accessed Jun 13 2018].

Evaluation Building Blocks: A Guide - McKegg, K.; Oakden, J.; Wehipeihana, N.; King, Julian (Kinnect Group, 2018)
This guide presents the Kinnect Group’s approach to evaluation. Developed through ten years of collaborative work, it has been well tested. While there are many other guides to evaluation and different ways to do it, our approach emphasises the place of evaluative reasoning in evaluation. The guide draws on the work of many evaluation theorists, as well as our practice-based body of knowledge. We hope that using the building blocks as explained in the guide will help you in your endeavour to do credible and useful evaluation. We find this approach works for us. Our clients tell us it gives them meaningful and insightful findings that they can use to take action. Our view to intellectual property is simple. What you read is yours to use. We just ask that you cite the guide when you draw from it. For those of you who engage with this guide and use it in your practice, we look forward to hearing from you. We are particularly interested in feedback where you find aspects of the guide work well for you. In that way we can all continue to build and evolve our practice.

Dynamic gridlock: Adaptive Humanitarian Action in the Democratic Republic of Congo - Obrecht, Alice (ALNAP Country Study, 2018)

Knowledge Management strategies and processes in Agile Software Development: a systematic literature review - Ouriques, Raquel Andrade Barros; Wnuk, Krzysztof; Gorschek, Tony; Svensson, Richard Berntsson (CoRR, 2018)
Knowledge-intensive companies that adopt Agile Software Development (ASD) relay on efficient implementation of Knowledge Management (KM) strategies to promotes different Knowledge Processes (KPs) to gain competitive advantage. This study aims to

Outcome Harvesting. Understanding social change results in complex circumstances - outcomeharvesting.net (2018)
This website is a source of applications, events and resources to support the development of a community of practitioners of Outcome Harvesting. BetterEvaluation is one of three sister sites of OutcomeHarvesting.net

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Social Impact Navigator - The practical fuide for organizations targeting better results - Phineo (Phineo, 2018)

Positive Deviance Initiative - Positive Deviance Initiative (2018)

Poverty Stoplight - povertystoplight.org (2018)
What is the Poverty Stoplight? The Stoplight is a tool that seeks to activate the potential of families and communities to lift themselves out of poverty. Using a technology platform, it offers a self-assessment survey and intervention model that enables people to develop practical solutions to overcome their specific needs. We work with organizations from different sectors around the world and bring together a network of powerful actors with one clear mission: eliminate poverty worldwide. The Stoplight Community is comprised of government agencies, private companies, small and medium-sized enterprises, non-profits, cooperatives, microfinance organizations, academic institutions, and sports clubs, among others.

What are you afraid of: Collective leadership and its learning implications - Raelin, Joseph A (Management Learning, 2018)
In this provocation, the author attempts to cite the advantages of collective leadership while acknowledging the objections and fears of challengers. Collective leadership is seen as remote because it defies the traditional view of leadership as an individualistic attractive quality that not only protects us but is efficient when applied. Nevertheless, the collective alternative may not only be advisable but required in a connected world featuring a networked economy. The contemporary socio-politico-economic environment requires the contribution of, creativity from, and collaboration among multiple agents providing a dynamic concentration of management and knowledge. If we are to accept and recognize the contribution of a collective leadership, its development would require an entirely different learning model. In particular, collective leadership development occurs as an acute immersion into the practices that are embedded within in situ material–discursive relations—in other words, among people, objects, and their institutions.

What We Do: Getting Beyond Statistics - Sense Guide (Sensemaker narrative monitoring, 2018)
Our approach Understanding daily life reality with micro-narratives Narratives and more specifically micro-narratives are a fundamental and ancient way by which humans interpret their experience and make decisions. SenseMaker® provides the ability to capture and understand those narratives. Through the web or app environment the software allows the capture of pictures, recordings and writing in various combinations to reflect how the respondents are making sense of the world. Reducing cognitive bias with self signification In a patented method, the respondent then interprets their own story into a series of abstract constructs (‘signifiers’) that feel more like a game than a survey, but allow profound meaning to emerge. This interpretation adds layers of meaning rather than simply interpreting the story and provides quantitative data to detect visual patterns among stories. The patterns are linked back to the original material enabling a deeper dive into individual stories. If the researcher first look for patterns in the metadata using statistical or visual tools, he or she is less likely to be biased by content and prematurely converge on an interpretation. Evidence based insights that enables action The output of SenseMaker® is statistical data backed up by explanatory narrative. This means that advocacy is an integral part of the system. Numbers on their own appear objective but are not persuasive; anecdotes on their own may be persuasive but are not objective. SenseMaker® puts the two together and provides a powerful means of persuasion. It also enables action. Instead of saying “How do we create a culture of X?” we say “How do we create more stories like this and fewer stories like that?” Then, as actions are initiated, we see the impact in real time.

Exploring new territories for evaluation - Sharp, Cathy (Collective Leadership for Scotland, 2018)
Drawing on action research, this paper recasts evaluation as ‘action inquiry’, an embedded evaluative learning practice that can help navigate complexity when enacting collective leadership. It is offered as an invitation to inquiry amongst a reasonably well-informed audience of policy makers and practitioners who work in and for public services. It will particularly interest those who provide research, evaluation and facilitation support, and those seeking to develop a more relational approach to research and evaluation. Action inquiry is a model of practising change together in environments where ‘nothing is clear, and everything keeps changing’ that significantly challenges the prevailing discourse on evaluation. Action inquiry can be wrapped around and enmeshed within initiatives and programmes that work with complexity - anywhere where success will depend on the quality of relationships that can be developed. The paper reviews some important interrelated concepts that underpin the ideals of collective leadership and public service reform and which confront deeply embedded traditional notions of leadership, expertise and participation. These offer important challenges to ideas about how change happens and recognise that relationships are at the heart of practising change. This warrants a re-examination of the high expectations of evidence-based or informed practice. Collective leadership makes new demands of evidence as it rests on help to determine ‘wise actions’ in real-life situations. This confronts the practical reality of how to work together in conditions often expressed as ‘dynamic’ or ‘turbulent’ and the added human complexities of power, emotions and relationships; too often these elements are denied or avoided aspects of a change process. Facilitated action inquiry makes these elements part of the conversations, in the midst of ‘work-as-we-are-doing-it’, to increase areas of choice for individuals and a group as a whole. Within public policy, there is an overwhelming amount of evidence about ‘what works’ yet change seems to be stubborn and slow. The paper explores some of the deep-rooted vestiges of a ‘hierarchy of evidence’ and assumptions about standardisation and generalisability that act as a ‘barrier to transformation’. These include the narrow framing of what counts as evidence and consequent relegation of community perspectives, lived experience and practice-based evidence. The paper acknowledges the clear appetite for different approaches to evaluation, especially those that better reflect deeply held values and avoid creating a culture of ‘gaming’, rooted in fear of failure and loss of funding, at the expense of learning. The need for new forms of developmental evaluative thinking, collaborative inquiry and action research to create embedded learning is well overdue. Action inquiry is a desirable and necessary response to the complex situations and challenges of human services and recognises the essentialness of knowledge co-production. It is a model of co-creation at every stage and endorses the idea that people learn from participation in evaluation and by testing theories of change through action. Action inquiry builds on the idea of inquiry, or a moment-to-moment awareness and quality of attention and draws from several elements of action research practice. It sees inquiry as an intervention in itself, one that furthermore, explicitly seeks to enhance the probability of the success of a programme, focus on learning, the collaborative development of practice-based knowledge and positive relationships. The paper highlights the importance of building inquiry into living systems, the role of facilitation, systemic inquiry, and evaluative thinking. It proposes an expansion of ideas of appreciation as a relational and collaborative practice that is a driver of emergence. Social recognition that acknowledges someone’s social value to the community and implies mutual moral obligations to cooperation and participation is particularly crucial in a work context that requires successful coordination and multiple contributions to achieve results across hierarchies of position, professional rank and sectors. Hence, appreciation goes beyond the idea of positivity to include social recognition, valuing more explicit forms of inquiry, building participants’ aspirations to design new social systems and acting in new ways to embed change. In developing this discussion, the paper contributes to emerging dialogues about the need for a model of ‘5th generation evaluation’. Such a model would be based on the idea that appreciative and challenging inquiry that is contextual, relational and open-minded will create better opportunities for change and development. The paper sets out some ‘provocative propositions’ that can help us to navigate this terrain, perhaps of a fledgling ‘5th generation approach’ to inquiry. Facilitated action inquiry can hold the key to developing both new knowledge and an adaptive, collaborative and improvisational skill-set, able to respond in new ways to systemic and complex issues on the ground. It’s common to hear the expression ‘it’s all about relationships’ and it is clearly time to shift our focus to relationships; not relationships as ‘things’, but as co-created and dynamic relational processes in which we are embedded. In this way we can bring new qualities to our talking to each other about our various and shared visions of a better future.

Exploring new territories for evaluation - Provocative propositions - Sharp, Cathy (2018)

Tips on Learning from Context: Formal and Informal Approaches to Understanding the Local Political Economy - Swift, Sarah (USAID, 2018)
Successfully adapting your programmatic efforts and policy engagement to the context depends on maintaining your understanding of that context. Given this, continuous learning and feedback loops--not only about your programming, but also about the environment you are working within--are important components of USAID’s work. Since our environments are always changing, in ways big and small, this can be intimidating. One can imagine a scenario where learning consumes the limited time and budgets available, especially for small programs. The question becomes: How can we learn enough, at the right times, to limit missed opportunities and warning signs, while avoiding being consumed by data collection and analysis that never influences our work? This document capitalizes on the experiences of USAID staff as well as emerging learning from other donors and researchers to highlight a range of approaches--formal and informal, time-bound and continuous--that can support ongoing learning within the operational tempo of a busy Mission team or Operating Unit.

Werner Ulrich's Homepage - Ulrich, Werne (2018)
This website provides a variety of resources from Werner Ulrich's work in a range of philosophical and research areas with a particular focus on his own work in critical systems thinking and practice or, Critical Systems Heuristics (CSH).

Discussion Note: Complexity-Aware Monitoring - USAID (Program Cycle, 2018)
This Discussion Note complements ADS 201 and outlines general principles and promising approaches for monitoring complex aspects of USAID development assistance. Complexity-aware monitoring is a type of complementary monitoring that is useful when results are difficult to predict due to dynamic contexts or unclear cause and-effect relationships. Key principles of the Program Cycle include applying analytic rigor, managing adaptively, and utilizing a range of approaches to achieve results. ADS 201.3.5.5 identifies three types of program monitoring – performance, context, and complementary. All USAID programming incorporates performance monitoring and should include context monitoring. Performance monitoring “is the ongoing and systematic collection of performance indicator data and other quantitative or qualitative information to reveal whether implementation is on track and whether expected results are being achieved.” Context monitoring is “[t]he systematic collection of information about conditions and external factors relevant to the implementation and performance of an operating units (OU’s) strategy, projects, and activities.” As stated in ADS 201.3.5.5, complementary monitoring may be used by missions and Washington OUs to complement performance and context monitoring in situations where results are difficult to predict due to dynamic contexts or unclear cause-andeffect relationships. This Discussion Note provides an explanation of when to use complementary monitoring approaches that are complexity-aware and summarizes the three principles of complexity-aware monitoring.

Evaluating development projects: exploring a synthesis model of the logical framework approach and outcome mapping - Yang, Ting (2018)
Under the current results-driven development agenda, sound evaluation, and a corresponding evaluation toolkit, need to be in place to examine whether and to what extent development interventions have achieved their targeted objectives and results, and to generate lessons for further development learning and improvement. My review of the literature shows that innovative and appropriate evaluation approaches are needed to address key challenges in evaluation such as the tension between learning and accountability objectives, the need to unpack the mechanisms linking outputs and outcomes or goal, and to add an actor perspective. Irrespective of project type, the Logical Framework Approach (LFA) is often a standard requirement of major official donor agencies on projects they fund, so as to fulfil bureaucratic imperatives. However, it is often considered inadequate in addressing key challenges in development evaluation. Given the dominant status of the LFA with such strong support from donors, it is helpful to seek a ‘middle way’: a combination of the LFA with other approaches in order to address some of its inadequacies, while satisfying donor agencies’ requirements. A synthesis of the LFA and Outcome Mapping (OM) is one such option. This thesis explores the practical value and usefulness of a synthesis model empirically. Applying the model in two case study aid projects, I found that it serves well as a theory-based evaluation tool with a double-stranded (actor strand and results chain) theory of change. The model helps reconcile learning and accountability and add explanatory power and an explicit actor perspective. It also helps establish causation and enable attribution claims at various results levels with its different elements. The model has some limitations but my results suggest it can be usefully adopted. The choice of its application depends on project evaluation context and purpose in specific cases.